Freedom of Speech in Digital Communication: Rafael Capurro’s Cultural Approach to Self-Formation - Dua, Mikhael (Jurnal Filsafat "WISDOM", 2024)
This article aims to explore the meaning of freedom of speech in Rafael Capurro’s writings. For this purpose, the article will consist of three parts. The first part will deal with the principle of freedom of speech which is embedded both in Western and Eastern cultures. The second part of the article will focus on the problematization of freedom of speech in digital communication, especially in cases of privacy and flourishing humanity. A harmonious social life and the flourishing of the human soul will be regarded as fundamental arguments of self-formation ethics in digital communication. Then, the third part of the article will trace out some of the implications of Capurro’s assessment of self-formation ethics as a basic argument for freedom of speech. In this final section, a discussion concerning the contribution of Capurro’s thoughts on criticizing pragmatic and intoxicant digital communication will be considered.